Neonatal Seizure: An Update - Rahman, Md Mizanur; Shaha, Narayan Chandra; Mannan, Md Abdul (Bangladesh Journal of Child Health, 2010)
Neonatal seizures continue to be a diagnostic and therapeutic challenge to the clinicians. Seizures can permanently disrupt neuronal development, induce synaptic reorganisation, reduce neurogenesis, alter plasticity and prime the brain to increased seizures later in life1. The prevalence of seizures is 2-3 /1000 live births in term and 10-15 /1000 in preterm deliveries2. Diagnostic and therapeutic interventions should thus be established promptly, for which proper classification and etiologic workup are pre-requisite. DOI: 10.3329/bjch.v32i1.6009 Bangladesh Journal of Child Health 2008; Vol.32(1): 21-28